PENGARUH MOTIVASI INTRINSIK, MOTIVASI EKSTRINSIK DAN KEDISIPLINAN TERHADAP KINERJA PEGAWAI PADA UPTD PUSKESMAS PERAWATAN NGLETIH - Zuyyina Alvi Mubarokah; Anwar Bowo Leksono; Udik Jatmiko (FKDP (Forum Komunikasi Dosen Peneliti), 2023)
This research explains the influence of intrinsic motivation, extrinsic motivation and discipline variables on employee performance at the Ngletih Nursing Health Center UPTD. The sample for this research was 44 respondents using a purposive sampling technique and the number of samples was determined by considering ASN. The results of the study obtained the regression equation Y = 15.007 + 0.054X1 + 0.084X2 + 0.350X3. It can be explained that intrinsic motivation partially has a significant influence on employee performance at the Ngletih Care Health Center UPTD. Extrinsic motivation partially has a significant effect on employee performance at the UPTD Ngletih Health Center. Discipline partially has a significant effect on employee performance at the UPTD Ngletih Health Center. Then intrinsic motivation, extrinsic motivation and discipline simultaneously have a significant influence on the performance of UPTD employees at the Ngletih Nursing Health Center. Apart from that, the coefficient of determination (R2) obtained a value of 94.6%, while the remaining 5.4% was influenced by other factors not included in this research. The implications of this research show that it is important to give appreciation, pay attention to get satisfaction from employees who have achieved achievements, pay attention to issues of concern between co-workers so that they are strengthened and always looked after. Agencies must be able to adopt policies in disciplining employees so that in the future it does not cause divisions so that the work process is not hampered.